2023
DOI: 10.1111/cts.13529
|View full text |Cite
|
Sign up to set email alerts
|

Digital health technology derived measures: Biomarkers or clinical outcome assessments?

Abstract: Digital health technologies (DHTs) present unique opportunities for clinical evidence generation but pose certain challenges. These challenges stem, in part, from existing definitions of drug development tools, which were not created with DHT-derived measures in mind. DHT-derived measures can be leveraged as either

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…18 Interpretation of ClinROs and PROs is further complicated by the fact that they may not be concordant with one another; for example, research has demonstrated that oncologists and nurses are more likely to record greater performance status than patients themselves. 19 In contrast to infrequent "snapshot" assessments of functional status collected through traditional COA methods, digitally enabled COAs and biomarkers 20 offer the opportunity to collect comprehensive and contemporaneous data to assess physical, cognitive, and behavioral function among patients with cancer in order to drive personalized medicine and gain insights into the consequences of anticancer therapies.…”
Section: Traditional Clinical Outcome Assessments Of Functional Statu...mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Interpretation of ClinROs and PROs is further complicated by the fact that they may not be concordant with one another; for example, research has demonstrated that oncologists and nurses are more likely to record greater performance status than patients themselves. 19 In contrast to infrequent "snapshot" assessments of functional status collected through traditional COA methods, digitally enabled COAs and biomarkers 20 offer the opportunity to collect comprehensive and contemporaneous data to assess physical, cognitive, and behavioral function among patients with cancer in order to drive personalized medicine and gain insights into the consequences of anticancer therapies.…”
Section: Traditional Clinical Outcome Assessments Of Functional Statu...mentioning
confidence: 99%
“…In contrast to infrequent “snapshot” assessments of functional status collected through traditional COA methods, digitally enabled COAs and biomarkers 20 offer the opportunity to collect comprehensive and contemporaneous data to assess physical, cognitive, and behavioral function among patients with cancer in order to drive personalized medicine and gain insights into the consequences of anticancer therapies.…”
Section: Traditional Clinical Outcome Assessments Of Functional Statu...mentioning
confidence: 99%
“…Here, we broadly examine the technology-based challenges facing the use of wearables by care delivery teams or those working in clinical trials within neuroscience. It is worth noting that real-world deployment of wearables in care delivery and clinical trial settings face different regulatory pathways and the reader is directed elsewhere for those topics (Vasudevan et al, 2022 ; Izmailova et al, 2023 ; Leyens et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Digital measure developers have started adopting this guidance to initiate regulatory submissions amidst discussion of a dedicated pathway for deploying digital measures as drug development tools (DDTs) 23 .…”
mentioning
confidence: 99%